Ergodicity of non-Volterra quadratic operators corresponding to permutations: Ergodicity of non-Volterra quadratic operators corresponding to permutations - Jamilov, U.U.; Khudoyberdiev , Kh.O. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
A point is called a periodic point of if there exists an so that . The smallest positive integer satisfying the above is called the prime period or least period of the point . A period-one point is called a fixed point of .